Multi-functional dressings for recovery and screenable treatment of wounds: A review - F. Moradifar; N. Sepahdoost; P. Tavakoli; A. Mirzapoor (Heliyon)
Considerable research has focused on advanced wound dressing technology over the past decade. The increasing emphasis on health and medical treatment is crucial to the modern healthcare system. Consequently, high-quality wound dressings with advanced standards are essential for superior medical care. Next-generation multifunctional wound dressings feature antibacterial properties, pain relief, biocompatibility, drug delivery, flexibility, and exudate absorption. Today, biomimetic models, tissue engineering, and synthetic skin are integrated with emerging wound healing technologies, offering a new perspective on wound management. Based on the classification model of multifunctional and advanced wound dressings, various AI-assisted wound management technologies are also highly efficient. The primary goals of advanced wound dressing technologies include faster wound healing, prevention of microbial contamination, preservation of skin aesthetics, reduction of treatment costs, and increased patient comfort. The latest technologies in this field not only promote faster healing and the treatment of deep wounds but also emphasize continuous control and monitoring of the healing process. These screenable wound dressings can be smart sensors to detect wound status based on parameters such as pH, moisture, temperature, and oxygen levels. This enables wound status monitoring and appropriate treatment responses. These technologies facilitate wound observation and monitoring, as well as the evaluation and control of the healing process through various models and strategies, such as the fabrication of functional nanomaterials, computer algorithms, and artificial intelligence. This review presents an overview of the most prominent new technologies in wound dressings, along with their innovative approaches.